2010
DOI: 10.1192/bjp.bp.110.083121
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of home treatment for elderly people with depression: randomised controlled trial

Abstract: Home treatment appears an effective and cost-effective service model for elderly people with depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 27 publications
1
48
1
5
Order By: Relevance
“…An English-language literature search to April 2013 revealed trials showing benefits similar to those of BTB (18, 30). A systematic review of 23 trials of community- and home-based interventions for late-life depression found better treatment acceptance and fewer nursing home admissions and inpatient days with such interventions compared with usual care (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An English-language literature search to April 2013 revealed trials showing benefits similar to those of BTB (18, 30). A systematic review of 23 trials of community- and home-based interventions for late-life depression found better treatment acceptance and fewer nursing home admissions and inpatient days with such interventions compared with usual care (45).…”
Section: Discussionmentioning
confidence: 99%
“…Community- and home-based nonpharmacologic depression treatment approaches are promising, but few are tailored to or specifically tested in older African Americans (18, 25, 28–30). …”
mentioning
confidence: 99%
“…Près de 80 % des participants présentent des symptômes de dépression de légers à sévères (selon l'échelle du CES-D), 98,5 % de détresse psychologique (selon le PARBAS) et 70 % de l'anxiété (selon l'échelle de Beck). La littérature tend à démontrer que les interventions à domicile seraient plus efficaces pour amener une réduction des symptômes de dépression à court et moyen terme versus les services en établissement (Klug et al, 2010). En ayant actuellement une offre de services qui soit autant à domicile qu'en établissement, une hypothèse peut être émise, soit que les SSSM 60+ devraient permettre de répondre à ces problé-matiques.…”
Section: Discussionunclassified
“…L'âge, le genre et le diagnostic principal figurent dans ces indicateurs (Lehman et al, 2004). Deuxièmement, des indicateurs d'offre de services, plus spécifique-ment les lieux des interventions (domicile/CLSC/autres) et le nombre d'interventions y apparaissent car ils influencent les répercussions des services sur certaines variables de santé, dont la dépression (Klug et al, 2010).…”
Section: Objectifs De L'étudeunclassified
“…d'une part, les intervenants soulignent que le fait de se déplacer tend à augmenter le sentiment d'empowerment chez les usagers qui le font et les aide à s'impliquer dans leur plan d'intervention. d'autre part, la littérature tend à démontrer que les interventions à domicile seraient plus efficaces pour amener une réduction des symptômes de dépres-sion à court et moyen terme (Klug et al, 2010). Le nouveau modèle de prestation de services dirige les intervenants vers des interventions en établissement, ce qui selon nous, réduira au cours des années (comme la tendance commence à le démontrer) les interventions de type face à face aux profits de celles téléphoniques.…”
Section: Resserrement Des Critères D'accès Et Délais D'attentes Questunclassified